The Gravity of Ideas: How Distance Affects Translations. (24th November 2017) - Sin, Isabelle
Abstract: I use newly digitised data on a million book translations for 1949–2000 to study the factors that affect the international diffusion of ideas carried by books. I estimate a gravity model and find translation flows decrease significantly with distance, although distance matters less in later years when the world is more highly globalised. Countries translate more from others that are culturally similar, but this explains none of translations' correlation with physical distance. Translations decrease faster with distance in developing countries, suggesting countries with the greatest potential benefit from adopting foreign ideas are least able to access them.